Critical success factors and benefits of social CRM implementation - Saag, Helen (2018)
The objective of the master thesis is to understand what are the critical factors that help to implement SCRM successfully, the benefits and impact to the organisation. Being successful is crucial because failure, the consequences to the revenue, profit and customer satisfaction can be disastrous. Semi-structured interviews were carried out with C-level managers, who directly connected to Social CRM (SCRM) projects and have already implemented or are about to implement SCRM within their organisation. The subjects were known large companies (start-ups and established organisations) worldwide from most of the sectors. With higher competition, fewer differentiated products, lower control over the customer, problems that can escalate fast, there are only a few moments, where organisations can differentiate during the customer journey. That means it is no longer possible to ignore customer requests. Organisations need to be where their customers are and they need to interact to avoid problem escalation. The best way to do it would be in Social Media as this is where most of the customers are. However, considering that already CRM implementation failure rate is very high – up to 70 percent (Woodcock, Green et al., 2011), it is unclear how to guarantee the success of SCRM implementation and what are the actual benefits that a company can expect. Would it be enough for the organisation just to implement a new tool to have better results or do organisations themselves need to adapt to succeed? Those are the main questions that this master thesis tries to answer.